2012
DOI: 10.1002/ejlt.201100384
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐mediated hydrolysis of flax seed oil for selective enrichment of α‐linolenic acid

Abstract: Polyunsaturated fatty acids (PUFA) are important ingredients of human diet because of their prominent role in the function of human brain, eye and kidney. α‐Linolenic acid (ALA), a C18, n‐3 PUFA is a precursor of long chain PUFA in humans. Commercial lipases of Candida rugosa, Pseudomonas cepacea, Pseudomonas fluorescens, and Rhizomucor miehei were used for hydrolysis of flax seed oil. Reversed phase high performance liquid chromatography followed by gas chromatography showed that the purified oil contained 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…The successful hydrolysis of oils and lipids using lipases has been already established in the literature 19–22. Candida rugosa lipase was employed in the present study to convert the triglycerides (WCO) into FFA.…”
Section: Methodsmentioning
confidence: 96%
“…The successful hydrolysis of oils and lipids using lipases has been already established in the literature 19–22. Candida rugosa lipase was employed in the present study to convert the triglycerides (WCO) into FFA.…”
Section: Methodsmentioning
confidence: 96%
“…3.1.1.3) that are the most widely used enzymes for biocatalytic applications . Lipase‐catalyzed transformations of oils are being performed in a wide range of reaction media . Among these, the biphasic system consisting of isooctane/buffer is the most frequently employed in order to increase solubility of non‐polar substrates .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has shown that increased consumption of long‐chain omega‐3 PUFA (n‐3 LCPUFAs), i.e., α‐linolenic acid (ALA), eicosapentaenoic acid (EPA), and DHA, could lower the risk of chronic diseases such as heart disease, cancer, and arthritis . ALA (C18:3, ω‐3), an essential fatty acid in the human diet and a principal n‐3 LCPUFA present in food and medicine, can effectively prevent a variety of diseases such as cardiovascular, hypertensive, inflammatory, and autoimmune disorders, depression, and certain disrupted neurological functions . Recently, the PUFAs of the desilked silkworm ( Bombyx mori L.) pupae oil were identified as a good source of ALA , which have attracted considerable attention for pharmaceutical and dietary purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment of n‐3 LCPUFAs has frequently been reported, including the purification of PUFAs by selective inclusion in guanidinium‐1,5‐naphthalenedisulphonate‐2‐methoxyethanol host networks , the enrichment of γ‐linolenic acid from plant oil by low temperature crystallization and improved fractional crystallization , the preparation of LCPUFAs by enzymatic acidolysis , the fractionation of polyunsaturated and hydroxy fatty acids by urea inclusion , and the purification of PUFAs by preparative column chromatography . These enrichment methods used to obtain PUFA‐rich fractions from natural oils are mostly associated with the number of double bonds and the degree of unsaturation in the carbon chain .…”
Section: Introductionmentioning
confidence: 99%